Chloroformamidine hydrochloride as a molecular linker towards efficient and stable perovskite solar cells. Issue 15 (22nd March 2023) - Li, Hui; Fu, Ping; Lu, Ruixue; Guo, Junxue; Guo, Xin; Li, Rengui; Li, Can
Abstract : A schematic of the modification mechanism of chloroformamidine hydrochloride (CFA) at SnO2 /perovskite (PVK) interface. Abstract : Interface engineering has become one of the important subjects in developing efficient and stable perovskite solar cells (PSCs). Herein, an interfacial molecular linker, chloroformamidine hydrochloride (CFA), is introduced to modify the properties of electron transport layers (ETLs) and modulate the interaction between the ETL and perovskite (PVK) layer via coordination/electrostatic coupling. It is found that the CFA molecular linker can passivate the oxygen vacancies/interfacial defects of SnO2 and construct an improved energetic alignment between the ETL and PVK layer. Consequently, a power conversion efficiency (PCE) of 23.47% with an open-circuit voltage ( V OC ) of 1.17 V for the target device is achieved. Moreover, unencapsulated PSCs based on CFA-modified SnO2 (CFA@SnO2 ) ETLs show enhanced thermal and moisture stability compared with PSCs without CFA modification. This work provides a feasible strategy to tune the interface between the ETL and PVK for efficient and stable PSCs.